DEGRADACIÓN DE TIERRAS Y TELEDETECCIÓN EN PLANICIES PRÓXIMAS A LA LOCALIDAD DE CENTENARIO, PROVINCIA DE NEUQUÉN - Luis Bertani; Oscar Peña (Boletín Geográfico)
In this paper the status of land degradation is analyzed in a plains sector near Centenario town in Neuquén Province. To carry on this analysis it was used digital processing of satellite images which were analyzed within the conceptual framework of landscape ecology (Forman and Godron, 1986). The study area comprises the old river terraces of Neuquén River, from a Pleistocene age, which have a sandy mantle that covers them, which usually constitutes the horizon where the soils that allow the development of a xeric vegetation, typical of the arid environments, in the eastern part of the Neuquén Province. This place is exposed to intense human activity for more than 50 years, related to hydrocarbon extraction what should be added, given the proximity of urban centers, the permanent removal of plant species for use as fuel. In addition to the information obtained during the field trips and the analysis of the background to this, the methodology involves the use of GIS Idrisi (Kilimanjaro version) for the digital processing of Landsat ETM satellite imagery provided by CONAE. The results were compared with information obtained from various field trips, and to recognize different matrices, patches and corridors, according to the methodology of Landscape Ecology.